Competition Tracker (New Delhi, 2014)
The Competition Act, 2002 confers upon the Competition Commission of India the responsibility to protect the interests of consumers and ensure freedom of trade in the country. The Competition Act is essentially an economic law that involves multidisciplinary approach. It is beneficial legislation which applies to all enterprises irrespective of origin, form or structure of ownership. To take informed decisions, the stakeholders often look for an authentic compendium of orders passed by the Competition Commission of India as the evolution of information jurisprudence is in a nascent stage in Indian jurisdiction. The present compendium on the subject has been compiled to fulfil this requirement. We are confident that it will be immensely useful to a wide array of audience including consumers, enterprises, advocates, corporate professionals and academics
Keywords: Competition Act